Assessment of Prolonged Physiological and Behavioral Changes Associated With COVID-19 Infection - Radin, Jennifer M. (JAMA Netw Open, 2021)
This cohort study examines the duration and variation of recovery among COVID-19–positive verses COVID-19–negative individuals.